1992
DOI: 10.1152/ajpheart.1992.263.1.h20
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of chronic coronary stenosis resulting in hibernating myocardium

Abstract: An experimental animal model of hibernating myocardium is presented. Sixteen animals were initially prepared of which seven were selected for final review. Hearts were instrumented in two separate surgical procedures such that maximum phasic flow velocity in the left anterior descending (LAD) coronary artery was reduced by 50% and followed over 1 wk. Regional shortening declined at 1 wk to 62% of aerobic values (P less than 0.048) and did not improve over 2 h reperfusion. Metabolic determinations, obtained aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…1,16 Similarly, several studies also demonstrated a maintained flow/function relationship in the presence of reduced myocardial blood flow induced by coronary stenosis, so called short-term hibernation. 11,[17][18][19][20] However, no study has reported the flow/function relationship during persistent stunning. In the present study, persistent myocardial stunning was maintained in response to the 6 episodes of repetitive coronary stenosis and reperfusion.…”
Section: Flow/function Relationship During Persistent Myocardial Stunmentioning
confidence: 99%
“…1,16 Similarly, several studies also demonstrated a maintained flow/function relationship in the presence of reduced myocardial blood flow induced by coronary stenosis, so called short-term hibernation. 11,[17][18][19][20] However, no study has reported the flow/function relationship during persistent stunning. In the present study, persistent myocardial stunning was maintained in response to the 6 episodes of repetitive coronary stenosis and reperfusion.…”
Section: Flow/function Relationship During Persistent Myocardial Stunmentioning
confidence: 99%
“…Numerous models have been established for what is currently referred to as acute or short-term hibernation, [5][6][7][8][9] but few long-term models exist that have documented both continuous monitoring of CBF reduction in the conscious state and an associated histopathological evaluation of the AAR. Some of the current models of chronic hibernation, although they document reduced mechanical function after chronic coronary artery stenosis, either have not measured CBF 10,11 or have measured CBF but found it not to be reduced. [12][13][14][15] Importantly, in many recent studies in patients with hibernating myocardium, CBF has been measured with positron emission tomography and also been found not to be reduced substantially.…”
mentioning
confidence: 97%
“…For example, circumflex ameroid models (rapidly progressing stenoses) in dogs usually have normal resting function, with a well-developed collateral circulation, yet hibernating myocardium can develop when source collateral flow is limited. 2,22 Bolukoglu et al 23 produced a near-critical stenosis in swine, but flow reserve was not continuously monitored, and hyperemic flow at the end of the study was not lower than control. Although regional function was depressed in this model, resting perfusion was normal, consistent with chronic myocardial stunning.…”
mentioning
confidence: 99%